2007
DOI: 10.1021/la7007107
|View full text |Cite
|
Sign up to set email alerts
|

Wetting-Induced Formation of Quasiperiodical Wrinkling Patterns in Alginate-Based Coatings

Abstract: We present the results of systematic model experimental investigations on wrinkling instabilities which develop on alginate-based coatings when they are wetted by swelling electrolyte drops. The wrinkles first appear randomly within the wet spot, before they selectively protrude out around the periphery in a quasiperiodical wrinkle pattern. We discuss the critical parameters that drive the emergence (ionic strength and swelling rate) and spatial feature (size and periodicity) of these swelling-induced structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…PS‐Ti multilayers put in contact with toluene vapors can generate various wrinkled patterns, considering that solvent diffusion is equivalent to an increase of temperature for the PS layer inducing a drastic decrease of elastic modulus. Baffoun et al reported a type of instability which involved the dissolution of the polymeric substrate by the solvent drop and resulted in the formation of finger patterns. While the formation of peripheral corrugation was due to the upward stretching force exerted by the underlying droplet composed of etchant and etching byproducts .…”
Section: Resultsmentioning
confidence: 82%
“…PS‐Ti multilayers put in contact with toluene vapors can generate various wrinkled patterns, considering that solvent diffusion is equivalent to an increase of temperature for the PS layer inducing a drastic decrease of elastic modulus. Baffoun et al reported a type of instability which involved the dissolution of the polymeric substrate by the solvent drop and resulted in the formation of finger patterns. While the formation of peripheral corrugation was due to the upward stretching force exerted by the underlying droplet composed of etchant and etching byproducts .…”
Section: Resultsmentioning
confidence: 82%
“…These final drying spots and crystallization patterns, of which a general view is shown in Figure 1, are composed of an assembly of well-defined dendrites crystals. Compared to most reported wetting-induced patterns in polymer coatings, 1,4,5 the self-assembly structures appearing here originate directly from molecular-scale interactions between randomly distributed chains, leading to unrevealed crystallization patterns in a polymer, which usually forms crystalline phases only under strong and oriented stress fields. 6,7 Indeed, alginate is a polysaccharide whose chains consist of regularly alternating blocks of L-guluronic acid (G) n , D-mannuronic acid (M) m , and (MG) p residues (Figure 2) which have strong conformational differences.…”
Section: Introductionmentioning
confidence: 77%
“…5f), characteristic of swelling-induced wrinkles in SA-based coatings. 25 Though these fibrillar dendrites that definitely constitute SA/NPs composite hydrogel microfibers were made stable over months (in ambient conditions) upon gelation, it was practically impossible to detach and collect them from the substrate and the under-layer film, for any use at the lab-scale. To circumvent this, we used a microgrooved PDMS support as a template to fabricate the ''isolated'' composite hydrogel microfibers, using the principle of capillary-driven suction and filling of such microchannels by a liquid (Fig.…”
Section: Drying Of the Bi-component (Mixed Sa/nps) Solutionsmentioning
confidence: 99%